Intravitreal conbercept for chronic central serous chorioretinopathy with occult CNV: a retrospective clinical study based on multimodal ophthalmic imaging - Suyu Wang; Jiajun Li; Zhipeng Yan; Qin Jiang; Keran Li (Frontiers in Medicine)
PurposeThis study aimed to evaluate the therapeutic efficacy and safety of intravitreal conbercept in patients with chronic central serous chorioretinopathy (cCSC) complicated by occult choroidal neovascularization (CNV), and to explore its potential in improving visual function and various ophthalmic parameters.MethodsThis retrospective, longitudinal, comparative study included 50 patients diagnosed with cCSC and occult CNV. Patients underwent intravitreal conbercept injections and were monitored over a six-month period. Comprehensive ophthalmic evaluation included best-corrected visual acuity (BCVA), central macular thickness (CMT), subretinal fluid (SRF) status, subfoveal choroidal thickness (SFCT), and optical coherence tomography angiography (OCTA). OCTA parameters such as foveal avascular zone (FAZ) area and CNV lesion characteristics were analyzed pre- and post-treatment. Patients were categorized based on changes in CNV lesion size to identify prognostic factors influencing treatment response.ResultsSignificant improvements were observed in mean BCVA from baseline (0.78 ± 0.50 vs. 0.32 ± 0.31, p < 0.01) in all 50 eyes of the patients, except for one eye. Additionally, there were significant improvements in CMT, SRF status, SFCT, FAZ area, and CNV lesion size post-treatment (p < 0.05). Pearson correlation analysis indicated a positive correlation between baseline BCVA and CMT (r = 0.3615, p = 0.0116). Changes in BCVA post-treatment correlated with alterations in CMT, SRF diameter, and CNV lesion size. Patients with a favorable treatment response had significantly lower baseline CMT (312.17 ± 57.39 vs. 428.86 ± 114.54, p < 0.05) and CNV vessel diameter (17.46 ± 2.72 vs. 24.84 ± 4.02, p < 0.01) compared to those with unfavorable responses.ConclusionIntravitreal conbercept injection was found to be safe and effective in improving BCVA and various ophthalmic parameters in patients with cCSC complicated by occult CNV, with no significant adverse effects observed during the study period. Baseline CMT, SRF diameter, CNV lesion size, and mean CNV vessel diameter were identified as valuable indicators for assessing treatment response and prognosis. These findings provide important insights for the clinical management and prognostic evaluation of cCSC patients with occult CNV, highlighting the utility of multimodal imaging in assessing treatment outcomes.